1994
DOI: 10.1177/42.12.7983361
|View full text |Cite
|
Sign up to set email alerts
|

Localization of sugar-binding sites in Staphylococcus aureus using gold-labeled neoglycoprotein.

Abstract: We studied post- and pre-embedding staining of sugar-binding sites on thin sections of Staphylococcus aureus with an electron microscopic neoglycoprotein-gold technique. Although gold particles of cellobiosyl bovine serum albumin (BSA)-glycosylated BSA-, lactosyl BSA-, and melibiosyl BSA-gold did not label, heavy labeling of N-acetylglucosaminide-BSA-gold was observed in both the cell wall and the cytoplasm on Spurr-embedded thin sections of S. aureus. Inhibition of labeling with wheat germ agglutinin-biotin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Colloidal gold particles (15 nm) were prepared according to the method of Frens [6]. Complexes of WGA-gold and neoglycoprotein-gold were prepared as we described previously [4,5]. In brief, the optimal amounts of WGA and GlcNAc-BSA for stabilization of 10 ml of colloidal gold particles were determined by the salt flocculation test [7].…”
Section: Colloidal Golds and Conjugationmentioning
confidence: 99%
See 1 more Smart Citation
“…Colloidal gold particles (15 nm) were prepared according to the method of Frens [6]. Complexes of WGA-gold and neoglycoprotein-gold were prepared as we described previously [4,5]. In brief, the optimal amounts of WGA and GlcNAc-BSA for stabilization of 10 ml of colloidal gold particles were determined by the salt flocculation test [7].…”
Section: Colloidal Golds and Conjugationmentioning
confidence: 99%
“…Here we show that a lectin and a synthetic neoglycoprotein agglutinate S. saprophyticus. Then we applied the gold labelling technique, which we have shown previously to be useful for localization of lectins or carbohydrates [4,5], and found that these molecules are involved in agglutination of S. saprophyticus and erythrocytes.…”
Section: Introductionmentioning
confidence: 99%